2022
DOI: 10.3390/foods11070944
|View full text |Cite
|
Sign up to set email alerts
|

Application of Untargeted Metabolomics to Reveal the Taste-Related Metabolite Profiles during Mandarin Fish (Siniperca chuatsi) Fermentation

Abstract: Spontaneous fermentation is a critical processing step that determines the taste quality of fermented mandarin fish (Siniperca chuatsi). Here, untargeted metabolomics using ultra-high-performance liquid chromatography coupled with Q Exactive tandem mass spectrometry was employed to characterize the taste-related metabolite profiles during the fermentation of mandarin fish. The results demonstrated that the taste profiles of mandarin fish at different stages of fermentation could be distinguished using an elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 43 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…These peptides provide the taste background and enhance other tastes [ 31 ]. Some small peptides, such as glutamic-acid-containing peptides, also exhibit an umami taste [ 31 ], and peptides containing bitter amino acids, such as valine, leucine, and phenylalanine, exhibit bitterness [ 31 , 38 ]. In this study, moromi-2 showed the most intense umami taste, but there was no difference in bitterness between moromi samples ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…These peptides provide the taste background and enhance other tastes [ 31 ]. Some small peptides, such as glutamic-acid-containing peptides, also exhibit an umami taste [ 31 ], and peptides containing bitter amino acids, such as valine, leucine, and phenylalanine, exhibit bitterness [ 31 , 38 ]. In this study, moromi-2 showed the most intense umami taste, but there was no difference in bitterness between moromi samples ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Succinic acid, heptanoic acid, and hexadecanoic acid have a salty-bitter taste, fatty odor, and mildly sweet taste, respectively, giving the harmonious flavor of Yakju [47][48][49]. Traditional-Soju has only one unique metabolite, malonic acid (5), which increases the sourness of Traditional-Soju (Figure 5C) [50,51]. We assumed that Traditional-Soju contained relatively higher amount of malonic acid than rice wine since it might be condensed by distillation and/or originated from additives.…”
Section: Discussionmentioning
confidence: 99%
“…Flavor is determined by the taste and odor of the food. Taste is reflected by the binding of water-soluble taste-presenting substances to human taste receptors [19]. The unique electrical signals generated by these compounds enable us to discern different tastes.…”
Section: Introductionmentioning
confidence: 99%